(untitled) (Web of Teachers: Inderscience Research, 2026)
During pregnancy, a woman’s body undergoes complex physiological, hormonal, and metabolic changes. In this period, external factors—especially harmful habits—directly and indirectly affect fetal development. Smoking, alcohol consumption, drug abuse, poor nutrition, chronic stress, sleep disorders, and physical inactivity are among the major modifiable risk factors that increase perinatal complications. This article systematically analyzes the pathophysiological mechanisms, clinical consequences, epidemiological evidence, and evidence-based medical, psychological, and social approaches to eliminating these harmful habits according to the IMRAD structure.